2006
DOI: 10.1111/j.1468-3148.2005.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Female Fire‐Setters with Mild and Borderline Intellectual Disabilities to a Group Intervention

Abstract: Background This report describes a cognitive behavioural group intervention for women with mild and borderline intellectual disabilities detained in a secure hospital setting because of their fire-setting behaviour. The study aimed to examine participants' motivations for setting fires, their responses to an intervention designed specifically for this group and to monitor their progress over an extended follow-up period. Methods A number of fire-specific and clinical assessments were administered before the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…The same group of authors (Taylor et al, 2006) reported a study on a group of six women detained in a specialist forensic intellectual disability service in England.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group of authors (Taylor et al, 2006) reported a study on a group of six women detained in a specialist forensic intellectual disability service in England.…”
Section: Discussionmentioning
confidence: 99%
“…Taylor, et al, 2006;Devapriam, Raju, Singh, Collacott, & Bhaumik, 2007), less than half of those with a fire setting history had a conviction for arson. This is probably because the blurred dividing line between criminal, and challenging behaviour in people with intellectual disability, which affects the reporting and recording of such behaviour (Holland, Clare, & Mukhopadhyay, 2002).…”
Section: Resultsmentioning
confidence: 99%
“…Over the past two decades, a small number of cognitive behavioral treatment packages (CBT) have been developed for use with mentally disordered firesetters (Hall, 1995;Swaffer, Hagget, & Oxley, 2001;Taylor, Thorne, Robertson, & Avery, 2002;Taylor, Robertson, Thorne, Belshaw, & Watson, 2006). However, these represent uncontrolled 'in house' therapy conducted with very small numbers of participants.…”
Section: Specialist Group Therapy For Psychological Factors Associatementioning
confidence: 99%
“…These latter property costs represent only a small amount of those incurred since they do not include some of the wider costs associated with firesetting (firefighting, or health costs or costs associated with wildfire damage). In the UK, there were 53,000 deliberately set fires and 451 fire- Over the past two decades, a small number of cognitive behavioral treatment packages (CBT) have been developed for use with mentally disordered firesetters (Hall, 1995; Swaffer, Hagget, & Oxley, 2001;Taylor, Thorne, Robertson, & Avery, 2002;Taylor, Robertson, Thorne, Belshaw, & Watson, 2006). However, these represent uncontrolled 'in house' therapy conducted with very small numbers of participants.…”
Section: Introductionmentioning
confidence: 99%
“…Gannon, Tyler, Barnoux and Pina (2012) noted that the only published descriptions of treatment for female firesetters concerned either tailored treatment for unusual cases or treatment for women in psychiatric facilities using CBT (e.g. Swaffer, Haggett, and Oxley, 2001;Taylor, Thorne, Robertson, and Avery, 2002;Taylor et al, 2006).…”
Section: Firesetting In Womenmentioning
confidence: 99%